The Role of Financial Planning in Improving Performance at SME UD. Sari Kelapa (Pendem Village, Junrejo District, Batu City, East Java) - Ardiyani Padu Lemba; Gunawan, Cakti Indra; Moh. Askiyanto (International Research and Development for Human Beings (IRDH), 2025)
SMEs are faced with many problems such as problems in financial management, competition, and market changes. With the role of financial management, business owners can plan, organize, manage, and control company resources to minimize losses by maintaining cash flow, and the survival of their business . This study aims to determine the financial planning needed to improve performance at SME UD. Sari Kelapa in Pendem Village Kec. Junrejo Batu City, East Java. This study focuses more on financial planning owned by SMEs UD. Sari Kelapa. The data collection method used in field research is primary data using interviews, documentation, and observation of business owners, supervisors or foremen, and employees of UD. Sari Kelapa. This study findings that SMEs should implement accounting-based financial management. So it can be concluded that the role of financial planning in improving performance. It is necessary to keep systematic records to determine the progress, decline, or development of the business. The addition of employees in managing finances is important, because in UKM UD Sari Kelapa there are no employees who manage financial management. However, complete financial records to determine the profit from each sale Improve business performance through financial planning so that it can see the progress of a business in its business performance. Financial planning carried out by SME UD. Sari Kelapa For revenue planning and expenditure planning at SMEs UD. Sari Kelapa's recording is not detailed and still does not use financial recording techniques by applicable SAK. Supporting factors in this study are income planning, expenditure planning, and financial goals. The inhibiting factors in this study are the individual's understanding of the role of financial planning, and the lack of specialized labor in the management of financial planning.